Grazing effects on species diversity across different scales are related to grassland types - Shijie Lv; Jiaojiao Huang; Hongmei Liu; Shengyun Ma (BMC Plant Biology, 2024)
Abstract Background Community species in different grassland types exhibit unique ecological traits and adaptation strategies, influencing the impact of grazing on species diversity at various scales. This study aimed to elucidate the response characteristics and rules of species diversity in different grassland types to grazing intensity by analyzing plant groups and species diversity. Results Grazing intensity, grassland type, and their interaction significantly affected α, β, and γ diversity. In meadow steppes, α and γ diversity conformed to the intermediate disturbance hypothesis, exhibiting a unimodal trend with increasing grazing intensity—initially increasing and then decreasing. In typical steppes, α, β and γ diversity showed no clear pattern in response to changes in grazing intensity. In desert steppes, α, β and γ diversity consistently declined with increasing grazing intensity. In meadow steppes, dominant and common species were crucial for sustaining community (α diversity) and landscape (γ diversity) diversity, whereas rare species primarily contributed to increased gradient differences (β diversity). In typical steppes, rare species were pivotal for community (α diversity) and landscape (γ diversity) diversity, while dominant and common species were important in reducing gradient differences (β diversity). In desert steppes, rare species were vital for maintaining community diversity (α diversity), dominant species played a key role in reducing gradient differences (β diversity), and common species were important for maintaining landscape-level diversity (γ diversity). Conclusions The characteristics and patterns of grazing intensity on species diversity at different scales, as well as the dominant plant group influencing plant species diversity at different scales, are controlled by grassland types. These findings highlight the need for tailored management strategies to conserve species diversity in various grassland ecosystems under different grazing pressures.